Simplify.

x^2/ x-1/ 3x^2/ x+4.

Simplify.

x^2+ 4x+ 3 /

2x-1/

x^2+x/

2x^2-3x+1.

Multiply.

2(x+3)/ x(x-1) * 4x(x+2)/ 10(x+3). Answer in simplest form.

I appreciate the help, thanks.

Guest Nov 27, 2017

#1**+3 **

Simplify.

x^2/ x-1/ 3x^2/ x+4.

There is no brackets so your meaning if not clear but this is the question that you have asked.

\(Simplify\\ x^2/ x-1/ 3x^2/ x+4\\ =(x^2/ x)\quad- ((1/ 3)x^2)/ x)\quad+4\\ =x \quad - \quad \frac{1x^2}{3}\div x\quad +4\\ =x \quad - \quad \frac{1x^2}{3x}\quad +4\\ =x \quad - \quad \frac{x}{3}\quad +4\\ =\frac{2x}{3}+4\\ =\frac{2x+12}{3}\)

Melody
Nov 28, 2017